Right Superior Mediastinal Lymph Node Dissection in Thoracoscopic Surgery Using a Bipolar Sealing Device. Issue 4 (June 2013) - Kamiyoshihara, Mitsuhiro; Igai, Hitoshi; Ibe, Takashi; Kawatani, Natsuko; Ohtaki, Yoichi; Shimizu, Kimihiro; Takeyoshi, Izumi
Objective: This study investigated the use of a new bipolar sealing device (BSD) in right superior mediastinal lymph node dissection during thoracoscopic surgery. Methods: The study population consisted of 42 consecutive patients undergoing lobectomy with right superior mediastinal lymph node dissection for primary lung cancer. Operative results were compared with those of conventional surgery in 42 background-matched controls. The primary endpoint for the present analysis was the success of right superior mediastinal lymph node dissection during thoracoscopic surgery using a BSD. The secondary endpoints included the duration of the operation, number of dissected lymph nodes, chest drainage volume and duration, postoperative hospital stay, morbidity, and mortality. Results: The BSD was used successfully in 42 patients. No significant difference in duration of lymph node dissection, chest drainage volume, drainage duration, or number of dissected lymph nodes was observed between the study group and the controls. Because of a learning curve, the procedure initially took more than 20 minutes to complete, but surgical time was reduced to approximately 15 minutes after the procedure was performed in 15 patients. Conclusions: Our method is safe and in no way inferior to the conventional procedure. The tendency of the learning curve suggests that a significantly shorter duration of lymph node dissection is possible using this method.